The Outlaws - Butterworth, William E. (William Edmund) (New York : Jove Books, 2012)
Charlie Castillos secret unit has been disbanded, but that doesnt mean hes out of business. A FedEx package arrives, bearing photos of barrels containing some of the most dangerous biohazard materials on Earth, all of which were supposed to have been destroyed during a raid on a secret Russian factory in the Congo. Who has them, and what do they want? Castillo has a feeling hes not going to like the answers.
Keywords: United States -- Army; Delta Force -- Fiction; Undercover operations -- Fiction; Thrillers (Fiction)